PROSES BISNIS TEH ORGANIK PADA AGROINDUSTRI PREMIUM TEA LUGU’S DI KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Hariance, Rika; Evaliza, Dwi; Dewanti, Aerini (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Knowing the business processes in agro-industrial activities is important to ensure product efficiency, quality and sustainability. Organic tea commodities have promising opportunities in the global market because demand for organic products continues to increase. Using a qualitative descriptive approach, this research was conducted at the local organic tea business Premium Tea Lugu's. Observations were made on business processes in the form of managing raw material procurement, processing and product marketing. The research results show that LUGU's Premium Tea collaborates with organic tea farmers in procuring raw materials. To ensure the availability of raw materials, farmers implement harvest rotation so that the production process remains sustainable. The product produced is powdered tea with product types: black tea, green tea and white tea. These products have different processing processes with a production time of 27.1 hours to produce black tea, 12.8 hours for green tea, and 2.5 hours for white tea. To increase sales, the marketing process carried out has taken into account the concept of product, price, place and promotion (4P). This powdered tea is available in packages of 10 grams to 1 kilogram with a selling price ranging from IDR 15,000 to IDR 2,500,000. Product purchases can be made online and offline. Promotion is carried out through personal sales, sales collaboration and participating in product bazaars. This agro-industrial business process has been carried out with good operational standards so that it can maintain production quality and sustainability.